(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2021)
Ziziphus mauritiana is used as a medicinal plants especially its fruit and leaf. In this work the leaf of Z. Mauritiana was screened, investigated qualitatively for its Phytochemical constituent and antimicrobial study carried out using disc diffusion method on some selected microorganisms. Elemental and anionic contents were carried out to determine the concentration levels of Zn, Pb, K, SO42-, Cl- and PO43-. The result of the phytochemical screening of the methanol leaf extractof Z. mauritiana revealed the presence of carbohydrates, tannins, saponins, cardiac glycoside and flavonoids. While alkaloids, terpenoids and phlobatannins were absent. The antimicrobial study revealed significant activity concentration-dependent at P<0.05 against Bacillus subtilis, Corynebacteria spp, Staphylococcus aureus, and Candida albicans, with highest zones of inhibitions of 14.50±0.71, 16.00±0.00, 18.00±0.00, and 14.50±0.71 respectively, although less effective than a standard drug (ciprofloxacine 500mg), While Pseudomonas aeruginosa, Salmonella typhi, Escherichiacoli, Klebsiella pneumonia and Streptococcus pyrogenes are resistant to the extract. Elemental and anionic contents indicate concentration levels of Zn, Pb, K, SO42-, Cl- and PO43- which were all within/below WHO/FAO permissible limits. Thus, the study has justified the traditional use of the plant for the management of microbial related diseases and could be safe and nutritious for consumption.